(untitled) (Muitas Vozes, 2021)
In this article, the issue of the verbal dimension of statements in the short story Happy birthday, by Clarice Lispector, is discussed. The central objective is to analyze how the author, based on certain linguistic strategies, builds stylistic marks to weave the narrative and constitute the thematic content. As a guide for this analysis, this study is based on the notion of style established from the theoretical reflections coined by intellectuals from the Bakhtinian Circle, such as interaction and enunciation. As a result of this investigation process, it was found that Lispector’s stylistic choices, such as the use of asyndetic structures and syntactic inversion, create effects that activate extraverbal in various aspects of the text.